Study on Position of Hindu Women’s Property Rights After 1956 Act: Examining the Legal Status and Empowerment of Hindu Women Through Property Ownership (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Women Constitute helping women to remain on their own feet on the off chance that we don't consider ways women can approach and power over cash, land and house. The initial step is to dismiss the blessing framework and request an offer in the family property. A lady ought to defeat the inclination that the home she imparts to her better half isn't hers. Furthermore, legitimately she ought to acquire and furthermore be the joint proprietor of her better half's property since she also places in her work. Women Constitute half of the total populace, perform multi-talented duties in the wedding home, in national development and planning process basically with pushes on wellbeing, education and business. Be that as it may, in spite of this, she respects to a class or gathering of society which gets unacceptable and deficient monetary help as their commitment to the development of family isn't viewed as beneficial work and they are not given any financial co-possession with equivalent rights. Oppression women is unavoidable to such an extent that it in some cases surfaces on an uncovered scrutiny of the law made by the assembly itself. This is especially so according to laws administering the legacyprogression of property among the individuals from a Joint Hindu family. It appears that this segregation is so profound and orderly that it has set women at the less than desirable end Hindu women's legitimate option to acquire property has been confined from the most punctual occasions in Indian culture. In this paper an endeavor has been made to consider the nature, advancement and the development of the idea of lady's property through different stages of development. Presumably, the privilege to property is significant for the freedom and development of a person. The exclusive situation of lady in any arrangement of law speaks to the idea and the sentiments of the network. Subsequently the exclusive status which a lady involved in Hindu law was a list of Hindu human advancement as well as right measure of the way of life of the Hindurace.